CONVEXITY OF PARAMETRIC WEIGHTED FUZZY DIVERGENCE MEASURES - Kumari, Santosh; Kumar, Surender (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper defines some weighted fuzzy parametric divergence measures such as Vs(A | | B; W) Ws(A | | B ; W) and Qs(A | | B ; W). Convexity, concavity and non-negativity of these measures are calculated by taking different values of parameters. For this we exploit Csiszar’s f-divergence and take the help of differential calculus.